Utilización del ordenador como herramienta para la organización profesional técnico pedagógico de los docentes de la Escuela Fiscal Mixta Bolivia Benitez del periodo lectivo 2011-2012. - Tituana Sari, Mónica Janeth (2012)
This paper is a compilation of content, data and interpretations statistics are the result of observation, the criterion of teachers and students, as the authorities that are involved in the process of implementing the topic of the thesis, it is drawn specific information of the educational reality of using the computer as a tool for teaching technical professional organization of teachers applied in Bolivia School Benitez.